Lord of the Pyrenees : Gaston Fébus, Count of Foix (1331-1391) - Vernier, Richard (Boydell Press, 2008)
The reign of Gaston III, Count of Foix and self-proclaimed sovereign Lord of Béarn, stands out as one of the rare success stories of the 'calamitous' fourteenth century. By playing a skilful game of shifting allegiances and timely defiance, he avoided being drawn into the conflicts between his more powerful neighbours - France and English Aquitaine, Aragon and Castile - thus sparing his domains the devastations of warfare. Best known as a patron of the arts, and the author of a celebrated 'Book of the Hunt', Fébus - as he styled himself - also prefigures the eighteenth-century 'enlightened despots' with his effort to centralize government, protect natural resources and promote enterprise. But a sequence of mysterious tragedies - the abrupt dismissal of his wife, the slaying of his only legitimate son - reveal the dark side of the brilliant and enigmatic 'Sun Prince of the Pyrenees'. RICHARD VERNIER is Professor Emeritus of Romance Languages and Literatures, Wayne State University. He is the author of 'The Flower of chivalry: Bertrand du Guesclin and the Hundred Years War'.